2018
DOI: 10.1016/j.powtec.2017.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Compaction properties of dry granulated powders based on Drucker–Prager Cap model

Abstract: Dry granulation by roll compaction is a process of size enlargement used to produce granules with a good flowability for further die compaction process. To gain in the understanding of how granulated powders behave during die compaction and why they exhibit different behaviors different from those showed by the feed powder, the main material parameters proposed in Drucker-Prager Cap (DPC) model, were determined for MCC101 powder and two granule sizes obtained from roll-compacted ribbons. For that, the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Because the individual Cu particles were nanoporous, with a relative density that decreased from 0.96 to ≈0.80 over the course of the consolidation experiment, the packing fraction at which jamming sets on in Figure 6 is in the range 0.62–0.78. It is interesting to note that the form of the geometric hardening curve for the Cu powder near the jamming transition closely resembles the strengthening behavior observed in previous work on jamming of a fluidized granular medium, [ 59–61 ] which revealed a 4× increment in strength as the powder charge jammed.…”
Section: Structural Evolution Of the Compactsupporting
confidence: 77%
“…Because the individual Cu particles were nanoporous, with a relative density that decreased from 0.96 to ≈0.80 over the course of the consolidation experiment, the packing fraction at which jamming sets on in Figure 6 is in the range 0.62–0.78. It is interesting to note that the form of the geometric hardening curve for the Cu powder near the jamming transition closely resembles the strengthening behavior observed in previous work on jamming of a fluidized granular medium, [ 59–61 ] which revealed a 4× increment in strength as the powder charge jammed.…”
Section: Structural Evolution Of the Compactsupporting
confidence: 77%
“…A commonly used model to describe the plastic behaviour, especially the compaction of porous media, is the Drucker-Prager Cap model (DiMaggio and Sandler, 1971). This model has been widely used to describe the behaviour of geomaterials (DiMaggio and Sandler, 1971;Grueschow and Rudnicki, 2005) as well as in applications where the focus is on mechanical compaction such as powder compaction modelling (Garner et al, 2015;Perez-Gandarillas et al, 2017). This model has a yield surface made of a line corresponding to a Drucker-Prager model to describe shear plasticity and an ellipsoidal Cap to describe compaction plasticity.…”
Section: Plastic Behaviourmentioning
confidence: 99%
“…During die compaction, the granules show different behaviour than feed powders and this observation had been reported many times in the literature as 'Loss of reworkability/loss of tabletability' leading to a reduction in tensile strength of tablets produced from granules [12][13][14]. It is also commonly observed that plastic materials are more sensitive to this phenomenon than brittle materials [15,16]. In the earlier paper [16], the understanding of how granules behave differently from feed powders had been studied for MCC101 powder.…”
Section: Introductionmentioning
confidence: 99%
“…It is also commonly observed that plastic materials are more sensitive to this phenomenon than brittle materials [15,16]. In the earlier paper [16], the understanding of how granules behave differently from feed powders had been studied for MCC101 powder. The analysis was based on Drucker-Prager Cap model (DPC), which characterizes the Elastic-Plastic behaviour of powders and takes into account the main properties of the compacted material (cohesion, internal friction, hardening and breaking under shearing stress).…”
Section: Introductionmentioning
confidence: 99%